THE USE OF NEUROPEDAGOGICAL TECHNOLOGIES IN THE EXPERIENCE OF FOREIGN COUNTRIES: A COMPARATIVE-PEDAGOGICAL ANALYSIS - Feruz Pardaboyevich Rakhmonkulov, Duvlanova Charos Shuxrat kizi (International Journal of Literature and Language Studies, 2026)
This article offers a comparative-pedagogical analysis of how neuropedagogical — or, more broadly, neuroeducational — technologies have been developed and deployed in the experience of foreign countries, with primary attention to higher-education contexts. Drawing on a structured narrative review of seminal international reports and peer-reviewed studies published between 1997 and 2014, the paper traces three converging strands: the OECD's policy framework for a learning science grounded in the brain; the Mind, Brain, and Education (MBE) research-and-practice movement in the United States; and the cautionary tradition, exemplified by Bruer, Goswami, Geake, Pasquinelli, Howard-Jones, and Dekker and colleagues, which has documented the prevalence of neuromyths and the difficulty of translating brain research directly into classroom prescriptions. The comparative analysis identifies four shared features across national contexts — institutional infrastructure for interdisciplinary research, policy uptake mediated by international organisations, persistent miscommunication between neuroscience and pedagogy, and growing emphasis on teacher education in the responsible use of brain-based claims — and three points of divergence in emphasis: the cognitive-developmental focus of UK and OECD work, the affective-social emphasis associated with US MBE scholarship, and the strong empirical focus on reading and numeracy circuits exemplified by French and Anglophone cognitive neuroscience. The paper concludes that neuropedagogical technologies are most productively understood not as direct translations of neuroscience into instruction but as cautious, interdisciplinarily mediated tools whose responsible adoption requires both methodological literacy and resistance to neuromyth.